1990
DOI: 10.1128/aac.34.11.2050
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-resistant methicillin-resistant Staphylococcus aureus in an acute-care hospital

Abstract: Use of ciprofloxacin as an alternative to vancomycin for treatment of methicillin-resistant Staphylococcus aureus infection has been paralleled by the emergence of resistant strains. This phenomenon has also been noticed in our hospital. To confirm our observation, methicillin and ciprofloxacin susceptibilities were tested by disk diffusion and broth microdilution techniques. We studied 83 methicillin-resistant Staphylococcus aureus isolates obtained from various sources over a 4-month period. Ciprofloxacin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…The antibiotic resistance patterns of pig MRSA, other than to methicillin, reflect the antibiotics used in veterinary medicine: tetracycline resistance is very common, whereas ciprofloxacin resistance has been found to be completely absent (de Neeling et al, 2007). This is very different to the situation in nosocomial MRSA strains, in which over 80% of MRSAs may be resistant to ciprofloxacin (Marangon et al, 2004;Raviglione et al, 1990), perhaps suggesting that ST398 is circulating in pigs and only infecting humans occasionally, or that pigs are an emerging reservoir of MRSA.…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 59%
“…The antibiotic resistance patterns of pig MRSA, other than to methicillin, reflect the antibiotics used in veterinary medicine: tetracycline resistance is very common, whereas ciprofloxacin resistance has been found to be completely absent (de Neeling et al, 2007). This is very different to the situation in nosocomial MRSA strains, in which over 80% of MRSAs may be resistant to ciprofloxacin (Marangon et al, 2004;Raviglione et al, 1990), perhaps suggesting that ST398 is circulating in pigs and only infecting humans occasionally, or that pigs are an emerging reservoir of MRSA.…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 59%
“…A concern about the clinical use of quinolones has been the rapid increase in resistance to ciprofloxacin in S. aureus, in particular MRSA, when ciprofloxacin has been introduced into widespread use within a medical center (9,36). In some institutions, most strains of MRSA are now quinolone resistant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, similar reductions in bacterial counts within valvular vegetations occur following treatment of experimental endocarditis caused by methicillin-susceptible S. aureus or MRSA with ofloxacin and with vancomycin (20). On the other hand, the rapid emergence of quinolone-resistant strains associated with quinolone use in some institutions raises concerns about the role of these agents in staphylococcal infection (8,36 In vivo procedures. Details of this small-inoculum prophylaxis model have been described previously (22,25,26).…”
mentioning
confidence: 99%
“…The initial concern that resistance in the gram-negative genera would emerge as a result of the introduction of the fluoroquinolones (for urinary tract infections) has not been borne out with the extensive use of this class for gram-negative infections (7). However, the increased use of the fluoroquinolones has apparently led to a dramatic increase in quinolone resistance among the staphylococci, particularly methicillinresistant S. aureus and Staphylococcus epidermidis (7,14). It has been suggested that this rise in resistance is due to the moderate activity of these drugs against staphylococci coupled with the low levels attainable in serum (4,7).…”
mentioning
confidence: 99%
“…A. (4,7,14), have pointed to the need to develop compounds with improved activity against S. pneumoniae and S. aureus. The insufficient activity of commercially available fluoroquinolones against anaerobes has precluded their use in infections caused by these organisms.…”
mentioning
confidence: 99%